A comparison of the effects of resistant starch types on glycemic response in individuals with type 2 diabetes or prediabetes: A systematic review and meta-analysis - Pugh, Jennifer E.; Cai, Mingzhu; Altieri, Nunzia; Frost, Gary (Frontiers in Nutrition, 2023)
Background: Type 2 diabetes (T2D) prevalence could reach 643 million by 2030, increasing incidences of cardiovascular disease and other comorbidities. Rapidly digestible starch elevates postprandial glycaemia and impinges glycaemic homeostasis, elevating the risk of developing T2D. Starch can escape digestion by endogenous enzymes in the small intestine when protected by intact plant cell walls (resistant starch type 1), when there is a high concentration of amylose (resistant starch type 2) and when the molecule undergoes retrogradation (resistant starch type 3) or chemical modification (resistant starch type 4). Dietary interventions using resistant starch may improve glucose metabolism and insulin sensitivity, however, few studies have explored differential effects of resistant starch type. This systematic review and meta-analysis aims to compare the effects of the resistant starch from intact plant cell structures (resistant starch type 1) and resistant starch from modified starch molecules (resistant starch types 2-5) on fasting and postprandial glycaemia in subjects with T2D and prediabetes. Methods: Databases (PubMed, SCOPUS, Ovid MEDLINE, Cochrane, Web of Science) were systematically searched for RCTs. Standard mean difference (SMD) with 95% confidence intervals (CI) were determined using random-effects models. Sub-group analyses were conducted between subjects with T2D versus prediabetes and types of resistant starch. Results: The search identified 36 RCTs (n = 982), 31 of which could be included in the meta-analysis. Resistant starch type 1 and type 2 lowered acute postprandial blood glucose [SMD (95%CI) = -0.54 (-1.0, -0.07)] and [-0.96 (-1.61, -0.31)]. Resistant starch type 2 improved acute postprandial insulin response [-0.71 (-1.31, -0.11)]. In chronic studies, resistant starch type 1 and 2 lowered postprandial glucose [-0.38 (-0.73, -0.02), -0.29 (-0.53, -0.04), respectively] and resistant starch type 2 intake improved fasting glucose [-0.39 (-0.66, -0.13)] and insulin [-0.40 (-0.60, -0.21)]. Conclusion: Resistant starch types 1 and 2 may influence glucose homeostasis via discrete mechanisms, as they appear to influence glycaemia differently. Further research into resistant starch types 3, 4 and 5 is required to elucidate their effect on glucose metabolism. The addition of resistant starch as a dietary intervention for those with T2D or prediabetes may prevent further deterioration of glycaemic control.